Special Issue "Hybrid Drugs: Design and Applications" - Parvesh Singh; Vipan Kumar (MDPI AG, 2023)
The widely held belief in the potential superiority of agents capable of modulating multiple biological targets has led to the adoption of molecular hybridization as an effective technique in the realm of drug discovery and development [...]